PENINGKATAN KESADARAN REMAJA TERKAIT HIV MELALUI PENDIDIKAN SEKSUAL SEJAK DINIeness regarding HIV through Early Sex Education - Darmawan, Taufan Citra; Santiasari, Retty Nirmala; Mahayati, Lina (STIKes William Booth Surabaya, 2023)
The HIV problem in Indonesia continues to increase every year. This increase is due to the lack of knowledge about HIV in society, especially in adolescent. Increasing adolescent knowledge is important because adolescents are the age stage most vulnerable to engaging in HIV risk behavior. One of the education that can be provided is sexual education. This education is important to increase understanding about sexuality, sexual diseases and risky sexual behavior for adolescent. After being given education, it is hoped that adolescent will be able to recognize and avoid HIV risk behavior. The aim of this activity is to provide education to adolescent to avoid risky actions and avoid HIV transmission. The implementation method is carried out by providing education to adolescent at secondary school level aged 15-19 years. Education is carried out by providing lectures and video presentations explaining sexual education. This action was carried out in 2 meetings. At each meeting, a pre-post test is given with questions to assess teenagers' understanding. The results of implementing early sexual education for adolescent found that 32 teenagers took part in the activity. After being given the questionnaire, there was an increase in knowledge before the education and after the education. Apart from that, when measuring the experience and satisfaction of teenagers after being educated, it was found that teenagers felt afraid of HIV transmission but were not afraid of HIV sufferers. 100% of teenagers say staying away from their actions is an important key in preventing HIV. 100% of teenagers are satisfied with the education provided. The results of the knowledge evaluation showed that 93.75% of teenagers understood the material provided. There are still teenagers who don't understand because in the middle of the process there are obstacles in absorbing information because these teenagers have to attend other activities.